Reframing the Role of Social Media in Enhancing Product Awareness in Indonesia’s Crop Protection - Mindy Rahayu; Leonnard Ong (Sekolah Tinggi Manajemen IPMI, 2025)
This study investigates how social media is revolutionizing marketing strategies and raising consumer awareness of products in Indonesia's crop protection sector. Building on earlier studies, the current study tackles the subject from the standpoint of market-driven innovation, highlighting the ways in which farmers' and retailers' decision-making is impacted by digital involvement. 33 farmers who were chosen by purposive sampling participated in the quantitative study. To assess the suggested hypotheses, data were first subjected to validity and reliability testing, and then correlation and regression analysis. According to the findings, all three constructs—social media usage, marketing campaign efficacy, and product awareness—showed strong validity (r-values above the r-table threshold) and excellent reliability (Cronbach's Alpha > 0.60). According to hypothesis testing, social media use significantly increases marketing campaign efficacy and product awareness, bolstering the idea that digital involvement may either replace or enhance traditional marketing channels. The report offers practical advice for agribusiness players, such as the necessity of relationshipdriven marketing efforts, farmer education initiatives, and localized content strategies. Geographic coverage and the omission of new digital platforms like short-form video applications are two examples of practical limits that are acknowledged. It is advised that future studies look into cross-platform tactics and the incorporation of e commerce into the distribution of agricultural inputs.